1996
DOI: 10.1093/nar/24.7.1369
|View full text |Cite
|
Sign up to set email alerts
|

Fully Edited and Partially Edited nad9 Transcripts Differ in Size and Both Are Associated With Polysomes in Potato Mitochondria

Abstract: Two classes of nad9 transcripts are present at different abundances in the steady-state RNA pool of potato mitochondria. The 5'- and 3' termini of the transcripts were determined by primer extension and S1 nuclease protection analyses respectively. Using two primer pairs that will either specifically amplify the larger transcript or amplify both the larger and the smaller transcripts in RT-PCR analyses it was found that the larger nad9 transcripts are partially edited, while the smaller transcripts are fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…In favour of this hypothesis, partially edited and unspliced transcripts were found associated with polysomes. 51,52 As a second hypothesis, PPR336 could have a direct function in mitochondrial translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In favour of this hypothesis, partially edited and unspliced transcripts were found associated with polysomes. 51,52 As a second hypothesis, PPR336 could have a direct function in mitochondrial translation.…”
Section: Discussionmentioning
confidence: 99%
“…39, derived from the work of Maffey et al 38 and Lu et al 51 Succinctly, a lysate obtained from 100 mg of S. tuberosum mitochondria was centrifuged through a 61% sucrose cushion at 235,000g for 2 h. The polysomecontaining pellet was further separated on 10-35% sucrose gradients centrifuged at 155,000g for 2 h. Fractions 1-17 (from top to bottom) were collected on the gradients and analysed on 10-17% SDS-PAGE. For Northern blot analysis, total RNA was extracted from 100 μl of each § http://www.matrixscience.com fraction, separated on 15% polyacrylamide gel, electrotransferred onto Hybond-N nylon membrane (Amersham Biosciences) and hybridised to an oligonucleotide probe specific for potato mt 5S rRNA (CATATGGCGCAAGAC-GATTC).…”
Section: Preparation Of Mitochondrial Polysome-enriched Fractionsmentioning
confidence: 99%
“…We suggest this heterogeneity is occurred according to RNA editing mechanism, which not exactly identified in plant till now (Aleel, 2011). Also, we excluded the effect of mtDNA copy on heterogeneous RNA editing because it is need different genomic nad3 sequences but investigators found that all clones of genomic nad3 gene of the same plant species have the same sequence, but the heterogenisity found in cDNA clones (Lu and Hanson, 1996;Kalinaty et al, 2008).…”
Section: Rna Editing In Nad3 Transcriptmentioning
confidence: 99%
“…Some examples showed that this incomplete editing results in the synthesis of polymorphic proteins within the organelle (e.g., (Lu and Hanson 1996)). Most of the edited nucleotides are found in the first and second codon positions causing amino acid changes in the corresponding sequences.…”
Section: Higher Plantsmentioning
confidence: 99%